Imaging of Hemorrhagic Stroke. Issue 5 (October 2016) - Hakimi, Ryan; Garg, Ankur
Abstract : ABSTRACT: Purpose of Review: Hemorrhagic stroke comprises approximately 15% to 20% of all strokes. This article provides readers with an understanding of the indications and significance of various neuroimaging techniques available for patients presenting with hemorrhagic strokes of distinct causes. Recent Findings: The most common initial neuroimaging study is a noncontrast head CT, which allows for the identification of hemorrhage. Once an intracranial hemorrhage has been identified, the pattern of blood and the patient's medical history, neurologic examination, and laboratory studies lead the practitioner to pursue further neuroimaging studies to guide the medical, surgical, and interventional management. Given that hemorrhagic stroke constitutes a heterogeneous collection of diagnoses, the subsequent neuroimaging pathway necessary to better evaluate and care for these patients is variable based on the etiology. With an increasing incidence and prevalence of atrial fibrillation associated with the aging population and the introduction of three new direct factor Xa inhibitors and one direct thrombin inhibitor to complement vitamin K antagonists, oral anticoagulant use continues to increase. Patients on oral anticoagulants have a sevenfold to tenfold increased risk for intracerebral hemorrhage (ICH). Furthermore, patients who have an ICH associated with oral anticoagulant use have a higher mortality rate than those with primary ICH. Despite the reduced incidence of hypertension-related ICH over the past decade, it is expected that the incidence of ICH will continue to increase. Summary: Neuroimaging studies are integral to the identification of hemorrhagic stroke, determination of the underlying etiology, prevention of hematoma expansion, treatment of acute complications, and treatment of the underlying etiology, if indicated. Neuroimaging is essential for prognostication and thus directly impacts patient care.